Retinal Microvascular Changes in Subtypes of Ischemic Stroke - Zhao, Ying; Yang, Bing; Xu, An-Ding; Ruan, Yi-Wen; Xu, Ying; Hu, Hui-Ling; Tan, Ze-Feng (Frontiers in Neurology, 2021)
Aims: Retinal microvasculature shares prominent similarities with the brain vasculature. We aimed to assess the association between retinal microvasculature and subtypes of ischemic stroke. Method: We consecutively enrolled ischemic stroke patients within 7 days of onset, who met the criteria of subtype of atherothrombosis (AT), small artery disease (SAD), or cardioembolism (CE) according to a modified version of the Trial of Org 10172 in Acute Stroke Treatment (NEW-TOAST). Digital fundus photographs were taken within 72 h of hospital admission using a digital camera (Topcon TRC-50DX), and fundus photographs were semi-automatically measured by software (Canvus 14 and NeuroLucida) for retinal vasculature parameters. Results: A total of 141 patients were enrolled, including 72 with AT, 54 with SAD, and 15 with CE. AT subtype patients had the widest mean venular diameter within 0.5–1.0 disk diameter (MVD0.5−1.0DD) followed by SAD and CE subtypes (86.37 ± 13.49 vs. 83.55 ± 11.54 vs. 77.90 ± 8.50, respectively, P = 0.047); CE subtype patients had the highest mean arteriovenous ratio within 0.5–1.0 disk diameter (MAVR0.5−1.0DD) followed by the AT and SAD subtype groups (0.97 ± 0.03 vs. 0.89 ± 0.99 vs. 0.89 ± 0.11, respectively, P = 0.010); SAD subtype patients were found with the highest mean venular tortuosity within 0.0–2.0 disk diameter (MVT0.0−2.0DD) followed by the AT and CE subtypes (1.0294 ± 0.0081 vs. 1.0259 ± 0.0084 vs. 1.0243 ± 0.0066, respectively, P = 0.024). After adjusting for clinic characteristics, MVD0.5−1.0DD was significantly different among AT, SAD, and CE subtypes (P = 0.033). By receiver operating characteristic curve analysis, MVD0.5−1.0DD predicted the AT subtype (area 0.690, 95% confidence interval, 0.566–0.815), with a cutoff value of 82.23 μm (sensitivity 61.1%, specificity 73.3%). Conclusion: Retinal MVD0.5−1.0DD (>82.23 μm) might be associated with the AT stroke subtype; however, we need large-scale prospective studies in future to explore the underlying mechanism and causal explanation for this finding.